Planning for Small-Scale Business (USK) Batik Wastewater Treatment Plant X Yogyakarta - Intan Rahmalia; Farhan Muhammad Hilmi; Iva Yenis Septiariva; Reifaldy Tsany Betta Aryanto; Sri Dewi Handayani; Yesaya Emeraldy Priutama; Ariyanti Sarwono; I Wayan Koko Suryawan (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Small scale business / Usaha Skala Kecil (USK) X currently does not have a batik wastewater treatment unit. This condition causes the possibility of contamination to water bodies. USK X wastewater treatment applications' planning needs to be carried out sustainably, namely by reusing water. The process units needed in this planning are the sequencing batch reactor (SBR) and constructed wetlands. The effluent of textile wastewater with this system for parameters BOD, COD, TSS, sulfide, total oil & fat, and color were 0.13 mg/L; 106.5 mg/L; 2.4 mg/L; 0.036 mg/L; 0.07 mg/L; and 90.67 PtCo, respectively. The dimensions of the SBR unit required are 0.75 x 0.6 x 1 m. Modification of the SBR unit uses an ozone generator to produce ozone gas which functions as oxidation of organic pollutants and colors in batik waste. After processing in the SBR unit, it is carried out using a constructed wetland with 2.56 m2.